Implikasi Putusan Mahkamah Konstitusi Nomor 85/PUU-XX/2022 terhadap Penyelesaian Perselisihan Hasil Pemilihan Kepala Daerah - Rezah, Farah Syah; Sapada, Andi Tenri (CV. Social Politic Genius (SIGn), 2024)
This study aims to analyze the juridical implications of Decision Number 85/PUU-XX/2022 for the dispute resolution of Regional Head Election results in Indonesia and examine the position and authority of the Constitutional Court following the decision. This research employs a normative legal research method with statutory and conceptual approaches. The analytical techniques used are qualitative-descriptive and interpretative analysis techniques to examine and interpret legislation, Constitutional Court decisions, and relevant legal literature. The results show that Decision Number 85/PUU-XX/2022 has re-established the Constitutional Court’s permanent authority to adjudicate disputes over Regional Head Election results, previously annulled through Decision Number 97/PUU-XI/2013. Decision Number 85/PUU-XX/2022 is based on a constitutional interpretation that there is no distinction between the General Elections regime and the Regional Head Election regime within the framework of the 1945 Constitution. The juridical implication of this decision is the establishment of legal certainty regarding the institution authorized to resolve disputes over Regional Head Election results, namely the Constitutional Court, with definitive authority that is no longer ad hoc. In addition, this decision can potentially increase the effectiveness of the dispute resolution of Regional Head Election results and strengthen the electoral democratic system at the local level. To strengthen the position and ensure the continuity of the Constitutional Court’s authority, it is recommended to amend Law Number 48 of 2009, Law Number 10 of 2016, and the 1945 Constitution to explicitly mention the Constitutional Court’s authority in adjudicating disputes over Regional Head Election results.